Strategi Membaca Metakognitif dan Pencapaian Membaca L2: Studi Korelasi EFL di Indonesia - Dewi, Leona Nine Angga; Endarto, Ignatius Tri (Al-Lisan: Jurnal Bahasa, 2022)
This study aimed to investigate how metacognitive reading strategies correlate with EFL learners’ achievement. Three types of metacognitive reading strategies were measured in this study, namely: global reading strategies, problem-solving reading strategies, and support reading strategies. The data collection was conducted with 56 participants from an ESP reading class at a private university in Yogyakarta. This study found that problem-solving reading strategies and global reading strategies correlated positively with students’ achievement, while support reading strategies correlated negatively with their achievement. However, those correlations were not statistically significant. Therefore, it indicates insufficient evidence to suggest that the same correlations also happened in the population or that the observed correlations might have occurred by chance. Despite the correlations not being statistically significant, in this research, the participants were sampled from the population with a 95% confidence level and a margin of error of 5%.In addition to the findings, this study provides teachers with an example of a framework for a needs analysis to measure their students’ metacognitive reading strategies and help them plan more informed reading instruction.